(untitled) (SAARC Journal of Agriculture, 2026)
The present study was conducted to assess arbuscular mycorrhizal (AM) fungal root colonization, spore population, and species diversity associated with Sorghum bicolor cultivated in different talukas of Solapur district, Maharashtra. Root and rhizosphere soil samples were collected from ten locations and analyzed using standard mycorrhizal assessment techniques. All sampled plants exhibited AM fungal colonization, indicating the widespread occurrence of AM fungi in sorghum rhizosphere soils. Root colonization ranged from 45% to 72%, while spore population varied from 15 to 140 spores per 100 g of soil, showing significant location-wise variation. Hyphal and hyphal with vesicular types of colonization were observed, with vesicular colonization predominating in most locations. A total of several AM fungal species belonging to the genera Glomus, Acaulospora, Entrophospora, Gigaspora, Scutellospora and Sclerocystis were recorded, with Glomus species being dominant across all sites. The study highlights the influence of soil and agro-climatic conditions on AM fungal distribution and emphasizes the importance of native AM fungi in maintaining soil biological health and supporting sustainable sorghum production under semi-arid conditions. SAARC J. Agric., 23(2): 111-118 (2025)